Assessment of Concept Maps Generated by Undergraduate Students about the Function Concept - ŞENGÜL, SARE (ELSEVIER SCIENCE BV, 2014)
This research aims to assess the concept maps related to the function concept generated by undergraduate students. In our study, firstly students were asked to write down the concepts that they know about the functions then generate a concept map by using these concepts. After this application a five-item questionnaire was also applied in order to get students' opinions about concept maps. The maps generated by students were analyzed according to the systematic of Varghese (2009) and the answers to the questionnaire were separately examined. It was observed from the findings that the students had difficulties in generating concept maps and relating the function concept with the other concepts. (C) 2013 The Authors. Published by Elsevier Ltd. Selection and/or peer-review under responsibility of Academic World Education and Research Center.
Keywords: Concept map; function; assessment